2017
DOI: 10.1038/srep43709
|View full text |Cite
|
Sign up to set email alerts
|

Functional annotation of sixty-five type-2 diabetes risk SNPs and its application in risk prediction

Abstract: Genome-wide association studies (GWAS) have identified more than sixty single nucleotide polymorphisms (SNPs) associated with increased risk for type 2 diabetes (T2D). However, the identification of causal risk SNPs for T2D pathogenesis was complicated by the factor that each risk SNP is a surrogate for the hundreds of SNPs, most of which reside in non-coding regions. Here we provide a comprehensive annotation of 65 known T2D related SNPs and inspect putative functional SNPs probably causing protein dysfunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
2
0
1
Order By: Relevance
“…The effect of these SNPs is increasingly evaluated by constructing polygenic risk scores (PRS), whereby the individual risk alleles are summed to provide a genetic risk for each individual in a population. Studies of type 2 diabetes PRS showed a significant association with risk of type 2 diabetes after adjustment for other phenotypic factors, and a study conducted among Europeans demonstrated a 9.4‐fold risk for individuals in the upper vs lower 2.5% of the PRS …”
Section: Introductionmentioning
confidence: 99%
“…The effect of these SNPs is increasingly evaluated by constructing polygenic risk scores (PRS), whereby the individual risk alleles are summed to provide a genetic risk for each individual in a population. Studies of type 2 diabetes PRS showed a significant association with risk of type 2 diabetes after adjustment for other phenotypic factors, and a study conducted among Europeans demonstrated a 9.4‐fold risk for individuals in the upper vs lower 2.5% of the PRS …”
Section: Introductionmentioning
confidence: 99%
“…Genetic information, with which one is born, offers a way to make early detection of risk. Genome-wide association studies (GWAS) identified multiple common variants associated with T2D 4-7 , renal 8,9 , cardiovascular diseases 10 , and hypertension 11 . Individually, these genetic variants account for only a small effect size but the combination of hundreds or thousands of them into polygenic risk scores (PRS) or genome-wide polygenic scores (GPS) was recently introduced to predict individual risk of diseases 12-15 including type 2 diabetes 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Felizmente, devido aos avanços contínuos fornecidos por estudos de associação genômica ampla (GWAS) e análises de sequenciamento de próxima geração, os dados genômicos e epigenéticos enriquecem o campo sobre o significado funcional dos SNPs de risco conhecidos. Embora a identificação do SNP de risco seja fundamental para ilustrar a relação entre as variantes humanas e o risco de distúrbios poligênicos, a maioria dos SNPs de risco reside em grandes íntrons ou distais aos exons codificadores, que no passado foram tratados como áreas de lixo no genoma humano [22]. Por isso, a anotação funcional é importante, fornecendo uma lista de SNPs de risco potencial, priorizados para a estimativa adicional da suscetibilidade a determinadas doenças nos indivíduos.…”
Section: Introductionunclassified